Content of vol. 21, 2021, Journal Scientific and Applied Research: Content of vol. 21, 2021, Journal Scientific and Applied Research - Boyanov, Petar (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
Content of vol. 21, 2021, Journal Scientific and Applied Research